ETIKA KOMUNIKASI GURU–PESERTA DIDIK DI ERA DIGITAL: TELAAH KRITIS ATAS RELASI PEDAGOGIS DALAM RUANG PEMBELAJARAN VIRTUAL - Ashifah, Dini; Karimatuzzahra, Naila; Khasanah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the ethics of communication between teachers and students in learning in the digital era, with pedagogical relations as the main focus of the study. The development of digital technology has transformed patterns of educational interaction from face-to-face communication into communication mediated by virtual platforms, instant messaging applications, social media, and online learning spaces. This transformation provides convenience in the learning process, but it also raises ethical issues, such as miscommunication, blurred professional boundaries, privacy violations, weak communicative empathy, and reduced emotional closeness between teachers and students. This article employs a descriptive qualitative approach using a literature study method through the examination of Indonesian academic books and relevant scholarly journals. The findings show that communication ethics in digital learning should not be understood merely as linguistic politeness, but also as the teacher’s moral responsibility to convey messages clearly, politely, empathetically, professionally, and with respect for students’ dignity. Teachers are required not only to master technology but also to build dialogical and humanistic communication so that virtual learning spaces continue to reflect the essence of education as a process of humanization. Thus, the ethics of teacher–student communication in the digital era serves as an important foundation for creating learning that is civilized, effective, and pedagogically responsible.